Hubungan program orientasi berbasis kompetensi dengan kinerja perawat baru - Wijaya, Dodi; Sitorus, Ratna; Handiyani, Hanny (Jurnal Keperawatan Soedirman, 2012)
Competency-based orientation program is a method of new nurse orientation programs. Research on cross-sectional descriptive correlational aimed to analyze the relationship of competency-based orientation program with the performance of new nurses in a inpatient unit at Husada hospital Jakarta. Results for 58 new nurses in the Husada hospital new nurses get a good view of interpersonal competence (72.4%), good technical competence (53.4%), good competence in critical thinking (58.6%). New nurses to see better performance (72.4%). Analysis showed any relationship between competency-based orientation program with the performance of new nurses (p = 0.000, CI: 0.336, 0.696). Competence of new nurses to form a new nurse has a professional performance so that important programs applied in any orientation of new nurses.